2012
DOI: 10.3748/wjg.v18.i45.6657
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of laparoscopicvsopen liver resection for hepatocellular carcinoma

Abstract: LLR appears to be a safe and feasible option for resection of HCC in selected patients based on current evidence. However, further appropriately designed randomized controlled trials should be undertaken to ascertain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 46 publications
7
99
2
3
Order By: Relevance
“…The results of the ongoing multicenter Orange-II trials assessing open versus laparoscopic left lateral hepatic sectionectomy within an enhanced recovery ERAS program may provide further evidence [55]. Twelve other systematic reviews were identified [56][57][58][59][60][61][62][63][64][65][66][67], 9 included meta-analysis comparing open versus laparoscopic liver surgery [58][59][60][62][63][64][65][66][67]. These meta-analyses concluded that LLR was associated with lower intraoperative blood loss, blood transfusion, postoperative complications and shorter hospital stay.…”
Section: Minimally Invasive Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the ongoing multicenter Orange-II trials assessing open versus laparoscopic left lateral hepatic sectionectomy within an enhanced recovery ERAS program may provide further evidence [55]. Twelve other systematic reviews were identified [56][57][58][59][60][61][62][63][64][65][66][67], 9 included meta-analysis comparing open versus laparoscopic liver surgery [58][59][60][62][63][64][65][66][67]. These meta-analyses concluded that LLR was associated with lower intraoperative blood loss, blood transfusion, postoperative complications and shorter hospital stay.…”
Section: Minimally Invasive Approachmentioning
confidence: 99%
“…These meta-analyses concluded that LLR was associated with lower intraoperative blood loss, blood transfusion, postoperative complications and shorter hospital stay. In addition, LLR reduced the incidence of liver failure and lowered postoperative ileus, while decreasing overall cost [60,63,68]. Moreover, it seems that patients with LLR had a faster oral intake and required less intravenous narcotic use [66].…”
Section: Minimally Invasive Approachmentioning
confidence: 99%
“…Studies from other centers showed similar advantages (7)(8)(9)(10)(11). In the western literature, indication of liver resection was greatly governed by the Barcelona Clinic Liver Cancer classification (12).…”
Section: Am Writing In Response To Professor Taizo Hibi's Editorialmentioning
confidence: 88%
“…Furthermore, these were found to be lower after LLR in 40 and 11 studies, respectively. Twelve meta-analyses and one Cochrane report were also analyzed [35][36][37][38][39][40][41][42][43][44][45][46][47] and consistent results included reduced blood loss and transfusions requirements when studied. This clearly shows that, in selected patients LLR when compared with open surgery is associated with reduced blood loss and subsequent transfusion rates.…”
Section: Discussionmentioning
confidence: 99%